The Use of Narco SS Score in Predicting Adverse Events in Children Undergoing Major Elective Abdominal Surgery at The University Teaching Hospital, Lusaka, Zambia - Martha Munkonka; Bruce C. Bvulani; Hazel Mumpanshya; Mulewa Mulenga (Wolters Kluwer Medknow Publications, 2024)
Background: The neurological, airway, respiratory, cardiovascular and other, with a subscore of surgical severity (NARCO-SS) is a scoring system which assesses the presence of systemic disease and the risk the operation poses to the patient. A number of patients that undergo major abdominal surgery suffer adverse events. The aim of the study was to determine the reliability of NARCO-SS in predicting peri-operative adverse events and to determine the risk factors for peri-operative adverse events in paediatric patients undergoing elective abdominal surgery. Materials and Methods: Prospective cohort study. Consecutively sampled patients from December 2019 to December 2020 were used. Patients scheduled for elective abdominal surgery were scored pre-operatively and end points were; when an adverse event occurred or up to day 30. Analysis of the reliability of the tool, bivariate and multivariate logistics regression was done. Results: One hundred and nineteen patients were enrolled and 49% of them had adverse events. Both bivariate and multivariate analyses showed no significant association between the NARCO-SS score and the occurrence of adverse events. The area under the receiver operating characteristics curve (area under the curve) of the NARCO-SS for adverse events was 0.518; there was a significant correlation between high scores and mortality. Longer duration of surgery and complex surgery were the risk factors for adverse events. Conclusions: The NARCO-SS score was found to be a poor predictor of adverse events with a fair inter-rater reliability as a scoring tool. Future research could evaluate a modification of neurological and airway categories.